2021
DOI: 10.52922/ti78375
|View full text |Cite
|
Sign up to set email alerts
|

Live streaming of child sexual abuse: an analysis of offender chat logs

Abstract: Live streaming of child sexual abuse presents challenges for law enforcement and policy development. This study analysed chat logs from seven offenders who watched and directed the sexual abuse of 74 children (mostly in the Philippines) via live stream. The study found that offenders paid facilitators and victims very small amounts of money (median A$51) to view the sexual abuse of children, and used mainstream messaging and video platforms (eg Facebook) to communicate and transmit the abusive materials. Two k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…It is important to note that most of the data in the victim and offender categories are based on cases from the Philippines. Further, four of the empirical studies are interrelated (Brown et al, 2020; Cubitt et al, 2021: Napier et al, 2021a, 2021b). For a summary of the most critical findings, see Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to note that most of the data in the victim and offender categories are based on cases from the Philippines. Further, four of the empirical studies are interrelated (Brown et al, 2020; Cubitt et al, 2021: Napier et al, 2021a, 2021b). For a summary of the most critical findings, see Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the characteristics, Cubitt et al (2021) analyzed the age of offenders of LSCSA and found that ages ranged from 20 to 76 years, and the average age of the offender was 52 years. Other studies have shown a range of between 50 and 60 years and 42 and 72 years of age (Brown et al, 2020;Napier et al, 2021a). These studies have used the same data source to some extent, and it is therefore unclear if there is any overlap in their findings.…”
Section: Offendersmentioning
confidence: 99%
See 3 more Smart Citations